Micropropagation of cork oak (Quercus suber L.) by apical bud culture from embryonic axes - El Kbiach, M. L.; Lamarti, A.; Abdali, A.; Badoc, A. (ACTA BOTANICA GALLICA, 2004)
To improve the in vitro germination and development of cork Oakembryonic axes, several mineral media were tested; Durzan medium modified 1/2 supplemented with 400 mg/l glutamine and 3% sucrose gave the best results. The action of BA alone or combined with other growth regulators was also studied. A low concentration (0.44 mu M) was found to give an acceptable percentage of plantlets. When combined with NAA, callogenesis was observed. The transfer of cultures in conditions of low luminosity led to the formation of several axillary buds. These buds were multiplied on a solid medium supplemented with GA(3) at low concentration. The buds were elongated, then rooted on a growth regulator-free medium after brief dipping in an auxinic solution. The rooted plants were potted on horticultural substrate.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: cork oak; Quercus suber; in vitro culture; embryon

Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M. L.; Lamarti, A.; Abdali, A.; Badoc, A. (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

Culture in vitro des bourgeons axillaires de Chêne-liège (Quercus suber L.). I—Influence des cytokinines sur l'organogenèse et la callogenèse de nœuds de plantules - Kbiach, M. L. El; Lamarti, A.; Abdali, A.; Badoc, A. (Bull. Soc. Pharm. Bordeaux, 2002)
Le débourrement in vitro des bourgeons axillaires de plantules de Chêne-liège a été abordé. L’influence de cytokinines ou de composés à activité cytokinine, seuls ou combinés aux auxines ou à l’AG3 , sur l’induction des bourgeons, l’élongation des pousses feuillées et la formation des cals a été étudiée. Dans le milieu de culture WPM, additionné des microéléments et du mélange vitaminique MS, la BA à 4,5 µM favorise la caulogenèse. Son association à d’autres régulateurs de croissance ne permet pas une amélioration du taux de débourrement. En revanche, à 4,5 µM et combinée à 7 µM d’ANA, la callogenèse est importante.
Keywords: bourgeons axillaires; call; callogenèse (PG); chêne-liège; cytokinines; débourrement in vitro